From the Madeira Chamber Orchestra to the Madeira Classical Orchestra: Contributions to an Organizational Analysis - Alves, J. Eduardo M. (2014)
In a moment when we are completing the “golden jubilee” of the Orquestra Clássica da Madeira, nothing more advisable than trying to promote a historical/sociological incursion on its foundation and evolution.In these brief notes, we are concerned mainly to examine the organizational Association, but also behavioral and functional implications, of those who joined the corporate boards of the Association, and detect in this organization, as sometimes in other social organizations, characteristics along its historical background, of systemic adaptation and development, typical of “learning organizations” (Gherardi, 2006).